Ethnographies and Health Reflections on Empirical and Methodological Entanglements (Springer International Publishing, 2018)
This edited collection explores the multiple ways in which ethnography and health emerge and take form through the research process. There is now a plethora of disciplinary engagements with ethnography around the topic of health, including anthropology, sociology, geography, science and technology studies, and in health care professions such as nursing and occupational therapy. This dynamic and evolving landscape means ethnography and health are entangled in new and different ways, providing a timely opportunity to explore what these entanglements do and affect in the social production of knowledge. Rather than discussing the strengths (and limitations) of ethnography for engaging with health, the book asks: what does ethnography enable, make visible and possible for knowing and doing health in contemporary research settings and beyond?